Feasibility of Plastic waste as Reinforcement in the Mechanical Properties of Stabilized Lateritic Soil Blocks - Sreekumar M.G (PREPARE@u® | IEI Conferences, 2021)
The popularity of earthen construction increases nowadays due to its sustainability features.  Stabilized earthen blocks are much accepted as an alternative building material from earthen building products against energy-intensive conventional building blocks.  The mechanical properties of stabilized earthen blocks can be further improved by the inclusion of waste materials. This study aimed to check the feasibility of using polypropylene and polythene plastic waste in stabilized masonry blocks manufacturing using locally available lateritic soil. Soil samples from two nearby locations and depths were collected and used in this study. An initial study conducted by manufacturing stabilized lateritic block specimens were made out of these samples with different mix proportions and tested. The optimized specimens based on strength were selected for further investigations using plastic wastes. Prospective results were obtained by this study. Both the plastic wastes inclusion showed enhanced strength and durability properties. The improvement can be much pronounced for polypropylene waste inclusion.